Rotavirus Genotypes in Hospitalized Children With Acute Gastroenteritis Before and After Rotavirus Vaccine Introduction in Blantyre, Malawi, 1997–2019. (9th October 2020) - Mhango, Chimwemwe; Mandolo, Jonathan J; Chinyama, End; Wachepa, Richard; Kanjerwa, Oscar; Malamba-Banda, Chikondi; Matambo, Prisca B; Barnes, Kayla G; Chaguza, Chrispin; Shawa, Isaac T; Nyaga, Martin M; Hungerford, Daniel; et al.
Abstract: Background: Rotavirus vaccine (Rotarix [RV1]) has reduced diarrhea-associated hospitalizations and deaths in Malawi. We examined the trends in circulating rotavirus genotypes in Malawi over a 22-year period to assess the impact of RV1 introduction on strain distribution. Methods: Data on rotavirus-positive stool specimens among children aged <5 years hospitalized with diarrhea in Blantyre, Malawi before (July 1997–October 2012, n = 1765) and after (November 2012–October 2019, n = 934) RV1 introduction were analyzed. Rotavirus G and P genotypes were assigned using reverse-transcription polymerase chain reaction. Results: A rich rotavirus strain diversity circulated throughout the 22-year period; Shannon (H′) and Simpson diversity (D′) indices did not differ between the pre- and postvaccine periods (H′ P < .149; D′ P < .287). Overall, G1 (n = 268/924 [28.7%]), G2 (n = 308/924 [33.0%]), G3 (n = 72/924 [7.7%]), and G12 (n = 109/924 [11.8%]) were the most prevalent genotypes identified following RV1 introduction. The prevalence of G1P[8] and G2P[4] genotypes declined each successive year following RV1 introduction, and were not detected after 2018. Genotype G3 reemerged and became the predominant genotype from 2017 onward. No evidence of genotype selection was observed 7 years post–RV1 introduction. Conclusions: Rotavirus strain diversity and genotype variation in Malawi are likely driven by natural mechanisms rather than vaccine pressure. Abstract : Combined G and P genotype diversity did not significantly change following rotavirus vaccine introduction in Malawi, but P genotype diversity increased in children aged >12 months. G3 rotaviruses reemerged and replaced G1P[8] and G2P[4] as the predominant genotype from 2017 onward.